In Vitro Antioxidant Activities of Three Selected Dates from Tunisia (Phoenix dactylifera L.) - Wissal Kchaou; Fatma Abbès; Hamadi Attia; Souhail Besbes (Journal of Chemistry)
Second-grade dates (Phoenix dactylifera L.), with hard texture, from three selected Tunisian cultivars (Allig, Deglet Nour, and Bejo) were analysed from their antioxidant activities using DPPH radical scavenging activity, FRAP assay, H2O2 scavenging activity, and metal chelating activity. Date extracts showed strong and concentration-dependant activity in all tested methods. The results showed that the best antioxidant activity was obtained in Allig, followed by Bejo and Deglet Nour. Total phenolics, total flavonoids, carotenoids, and tannins were determined spectrophotometrically in three date extracts. Results indicated that date contained significantly different amounts of these compounds. In fact, Allig presented the highest antioxidant compounds, followed by Bejo and Deglet Nour. Correlation analyses indicated a positive linear relationship between antioxidant activities and total phenolic and flavonoid content of date. This study demonstrates the potential antioxidant activity with Tunisian date, where we can use these natural extracts as food additives in replacement of synthetic compounds.